Analysis of The Implementation of The Role of Guru Penggerak in The Educational Environment of Mandailing Natal - Marwah, Marwah; Hakimah, Nur (DIDAKTIKA, 2025)
This paper discusses the analysis of the implementation of the role of the driving teacher in the education environment in Mandailing Natal. The findings indicate that through the driving teacher, creative, adaptive, and innovative learning processes, especially in the field of technology, have begun to develop. Through the implementation of the driving teacher program, teachers experience a learning system that focuses on students, thus developing individual student achievement rather than learning material. Furthermore, in the implementation of learning, driving teachers will be more innovative in more engaging learning methods and media in the classroom and adapt more and develop skills in the field of technology. In addition to the focus of driving teachers on self-development, they also focus on providing change and movement to non-driving teachers. However, these efforts often encounter obstacles because many non-driving teachers are still reluctant to change from habits that have been implemented in the learning experience. The findings also obtained most of the suggestions put forward by informants for the sustainability of the driving teacher program even though the minister has changed and the ideas are also different.